Mortality among injection drug users in northern thailand: A prospective cohort study - Quan V. (2017)
Objectives: To measure mortality rates and assess predictors of all-cause mortality in a cohort of Thai injection drug users (IDUs) who were enrolled and followed up from 2004 through 2006. Methods: In this prospective cohort study, we enrolled 314 community-dwelling IDUs (95% being men; 42% of ethnic minority; median age, 29 years [range, 18-69 years]) and followed up them at 6-month intervals. Mortality rates were calculated based on personyears of follow-up. Marginal Cox proportional hazards models for clustered data were constructed to determine the factors associated with all-cause mortality. Findings: During 445.7 person-years of follow-up, 17 of 314 (5.4%) IDUs died. The all-cause mortality rate was 3.8 per 100 person-years (95% confidence interval [CI] = 2.2-6.1). The standardized mortality ratio was 5.8 (95% CI = 3.5-9.1). The mortality rate among HIV-positive IDUs was 13.4 per 100 person-years (95% CI = 5.4 -27.6). In a marginal Cox proportional-hazards model for clustered data, the excess mortality was associated with HIV-positivity (hazard ratio [HR] = 7.0, 95% CI = 2.8 -17.6), benzodiazepine use (HR = 3.1, 95% CI = 1.1-9.4), and excessive alcohol consumption at enrollment (HR = 3.5, 95% CI = 1.3-9.1). Conclusions: The all-cause mortality among the drug injectors is high. The increased mortality was associated with HIV infection, benzodiazepine use, and excessive alcohol consumption. © 2010 American Society of Addiction Medicine.